Hal-Hal Yang Ada Hubungan Dengan Kanker Payudara Pada Penderita Di Beberapa Lokasi Di Wilayah Asia, Eropa Periode Tahun 2010 Sampai Dengan Tahun 2021 - Nur, Ajeng Maulidya; Murnita, Ika Azdah; Saleh, Adriandy (Fakultas Kedokteran Universitas Bosowa, 2024)
Breast cancer is a disease in which cells in the breast tissue change and divide uncontrollably and form lumps or masses, generally affecting women and mostly starting in the lobules (mammary glands) or in the ducts that connect the lobules to the nipple. The purpose of this study was to find out things that related with breast cancer there were family history of breast cancer, age at first menstruation, menopausal status, age at first childbearing, hormonal contraception, obesity, alcohol. The reasearch method was descriptive using literature objective approach on matters related to breast cancer in the journal of medical research in the literature. The results of the twenty studies analyzed showed that things that were related to breast cancer in several locations in Asia, Europe for the period 2010 to 2021, there were family history of breast cancer (p-value = <0.001), age at first menstruation (p-value = <0.001), menopausal status (p-value = <0.001), age at first childbearing (p-value = 0.002), hormonal contraception (p-value = <0.001), obesity (p-value = <0.001), alcohol (p-value = 0.006), had a significant relationship to breast cancer in several locations in Asia, Europe for the period 2010 to 2021. This research hoped to be used as an additional information for improving the role of health workers for prevent and handle the breast cancer.